Central Power and Decentralization: Peru, 1931 - Caravedo, Baltazar (1979)
One of the debates in the field of social sciences in Peru refers to the characteristics or nature of the ruling class. Today, despite the criticism, the use of the term "oligarchy" is the most common. Two recent publications persist in using that term, and have reintroduced an old argument in the current debate. Sociologist Henry Pease (1977) notes that the State "was directly controlled by a closed oligarchy where agricultural exporters had hegemony. They imposedtheir terms of foreign conduct until the 30's without question" (Pease, 1977: 217).